(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
The prose by Lesia Ukrainka was used for study of the verbalization of the hysteroid linquopsycho accentuation defined as lynquopsycho accentuation due to the principle of accentuation of linguistic mediums applied for determination of the relevant psychotype. It is established that application in the content of the literary text by Lesia Ukrainka of the somatic lexicon, fairy tale plots, mystic topics, her capacity to modeling unconven-tional images, her excessive lexicons demonstrate her propensity to creation of notions as day dream, fantasy, imagination in the combination with the applying in the discourse of the prose flexible communicative strategy, language presentation of the rapid change of the emotional conditions, doubts, contemplations, sense of pride what refers not merely to the specifics of the creativity as the process but to hidden form of hysteriodness. Thus congenital hystoroidness is the extra parameter affecting the peculiarity of imagination of the writer what promotes development of her linquocreаtivit personified in the formation of the fantastic poetic reality. So far we make conclusion that identification of the psycho linguistic accentuation and the character of the language mediums applied in the literary text is the principle idiocode of the cognitive construction of the elite language personality.